PENGEMBANGAN MODEL PEMBELAJARAN ATLETIK MELALUI MODIFIKASI PERMAINAN FORMULA 1 (RUN, JUMP, THROW) PADA SISWA KELAS VII SMP N 5 PEMALANG TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2013)
The research objective of this development are : Produces athletic development model of learning through game modification Formula 1 ( Run , Jump , Throw ) in accordance with the characteristics of class VII SMP N 5 Pemalang Pemalang district .The samples in this study using a random sampling technique , from classes VII consists of ten classes , taken one class is randomly selected as a research class . The data was collected and the evaluation sheet kuesioner.Teknik data analysis is descriptive analysis of data in the form presentase.Sedangkan suggestions and reasons for choosing the answers were analyzed using qualitative analysis techniques .The development of research results obtained by the research group of small trials 89 % ( good ) with psychomotor value of 90 % ( good ) , cognitive 89 % ( good ) and affective 89 % ( good ) and the research field trials gained 93 % ( very good ) with psychomotor value 93 % ( very good ) , cognitive 91 % ( very good ) , and affective 94 % ( very good ) .Conclusions of the research results suggested some of the following : Model Formula 1 game ( Run , Jump , Throw ) that have resulted from this research can be used as learning material for students of class VII athletic SMP Negeri 5 Pemalang .